On-farm diversification strategies and improved welfare of the immiserated rural smallholder farmer: Fallacy or realism?† - Lawrence G. Boakye (Cogent Social Sciences, 2021)
The promise and role of livelihood diversification has been taken up globally in the pursuit of mitigating risks confronting the immiserated rural smallholder farmer to improve living standards and viewed as paramount to advancing the welfare and prosperity of same. Yet, due to an apparent shift in interest and attention from on-farm to off-farm activities, much has not been documented on the impact of on-farm livelihood diversification strategies. Through the lens of a grasscutter domestication scheme implemented in Ghana by the Ghana Country Programme of ActionAid International, this paper explores the impact of such on-farm strategies on the welfare and livelihood of the immiserated rural smallholder farmer. Employing a focus group discussion to interview the beneficiaries, the paper identifies increased and alternative source of income, improved diet, and source of employment as major benefits of the scheme to report an apparent capacity and utility of on-farm livelihood diversification strategies to the socioeconomic empowerment of the immiserated rural smallholder farmer. The paper conveys that with further development through investments and improvements for greater operational efficiency, such strategies could have vast potential in building household capacities to improve living standards and welfare of same, and prove useful to advancing rural poverty reduction, and economic growth and development efforts. Implications are discussed.